Approach on runtime monitoring based on the embedded trusted platforms - Zhao-chang SUN; Jian-feng MA; Cong SUN; Di LU (网络与信息安全学报)
The state-of-art trusted computing platforms fall short of monitoring its own runtime security properties.In order to mitigate these problems,an approach on runtime monitoring for the embedded trusted platforms was proposed.With the automated code instrumentation and the runtime monitoring,that the runtime security functionalities were consistent with the design specifications of trusted computing platforms could be made sure.The system performance and states meet specific constraints could also be ensured.The runtime exceptions on the specific properties were handled in real-time.The experimental results show that with the increase on the number of monitoring nodes,the precision and real-time performance of proposed runtime monitoring increase.Meanwhile,the costs on the monitoring and the exception handling are moderate.